Beclin-1 dependent autophagy improves renal outcomes following Unilateral Ureteral Obstruction (UUO) injury - Lopez-Soler, Reynold I.; Nikouee, Azadeh; Kim, Matthew; Khan, Saman; Sivaraman, Lakshmi; Ding, Xiangzhong; Zang, Qun Sophia (Frontiers in Immunology, 2023)
Background Interstitial Fibrosis and Tubular Atrophy (IFTA) is the most common cause of long-term graft failure following renal transplant. One of the hallmarks of IFTA is the development of interstitial fibrosis and loss of normal renal architecture. In this study, we evaluated the role of autophagy initiation factor Beclin-1 in protecting against post-renal injury fibrosis. Methods Adult male wild type (WT) C57BL/6 mice were subjected to Unilateral Ureteral Obstruction (UUO), and kidney tissue samples were harvested at 72-hour, 1- and 3-week post-injury. The UUO-injured and uninjured kidney samples were examined histologically for fibrosis, autophagy flux, inflammation as well activation of the Integrated Stress Response (ISR). We compared WT mice with mice carrying a forced expression of constitutively active mutant form of Beclin-1, Becn1F121A/F121A. Results In all experiments, UUO injury induces a progressive development of fibrosis and inflammation. These pathological signs were diminished in Becn1F121A/F121A mice. In WT animals, UUO caused a strong blockage of autophagy flux, indicated by continuously increases in LC3II accompanied by an over 3-fold accumulation of p62 1-week post injury. However, increases in LC3II and unaffected p62 level by UUO were observed in Becn1F121A/F121A mice, suggesting an alleviation of disrupted autophagy. Beclin-1 F121A mutation causes a significant decrease in phosphorylation of inflammatory STING signal and limited production of IL6 and IFNγ, but had little effect on TNF-α, in response to UUO. Furthermore, activation of ISR signal cascade was detected in UUO-injured in kidneys, namely the phosphorylation signals of elF2S1 and PERK in addition to the stimulated expression of ISR effector ATF4. However, Becn1F121A/F121A mice did not reveal signs of elF2S1 and PERK activation under the same condition and had a dramatically reduced ATF level at 3-week post injury. Conclusions The results suggest that UUO causes a insufficient, maladaptive renal autophagy, which triggered downstream activation of inflammatory STING pathway, production of cytokines, and pathological activation of ISR, eventually leading to the development of fibrosis. Enhancing autophagy via Beclin-1 improved renal outcomes with diminished fibrosis, via underlying mechanisms of differential regulation of inflammatory mediators and control of maladaptive ISR.